Organizational Culture and Transformational Leadership on Employee Performance: the Mediating Role of Afective Commitment - Wibowo , Wibowo; Suhana , Suhana (Amkop Management Accounting Review (AMAR), 2025)
Abstract This study examines the effect of organizational culture and transformational leadership on employee performance. This study also examines the mediating role of affective commitment on the influence of the above variables. The research was conducted on 150 employees of BLUD Batang Hospital in Batang, Central Java. This research is a quantitative study by distributing questionnaires and using a Likert scale as a measuring tool. This research analysis tool is Structural Equation Modeling (SEM) AMOS . The findings of this study indicate that organizational culture has a significant positive effect on affective commitment, transformational leadership has a significant positive effect on affective commitment, organizational culture has a significant positive effect on employee performance. Other findings are transformational leadership has no significant effect on employee performance, affective commitment is proven to have a significant positive effect on employee performance. Affective commitment is proven to mediate the influence of organizational culture and transformational leadership on employee performance. This research has theoretical and practical implications.